1995
DOI: 10.1080/01904169509364989
|View full text |Cite
|
Sign up to set email alerts
|

Response of nitrogen fixation, nodule activities, and growth to potassium supply in water‐stressed broad bean

Abstract: Three-week-old nodulated faba bean plants were subjected to two levels of water stress (0.5 and 0.25 field capacity; soil water content of 20 and 10%) for five weeks. Half of the stressed plants was treated with potassium chloride (KC1) at 10 (K 1 ) and 150 mg (K 2 )/kg soil at the beginning of water deficit. Nodulation was examined and some nodule activities were assayed. Nodulation, nitrogenase activity, total nitrogen (N), and dry matter yield were significantly decreased by increasing stress but were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…It has been observed that negative effects of water stress can be reduced by potassium fertilization. This results supported to Mengel and Kirkby (1987), Abdalla andAbdclwahab (1995), andSangakkara et al (1995), Kaya et al (2001).…”
Section: Plant Dry Matter Yield (G/pot)supporting
confidence: 86%
See 1 more Smart Citation
“…It has been observed that negative effects of water stress can be reduced by potassium fertilization. This results supported to Mengel and Kirkby (1987), Abdalla andAbdclwahab (1995), andSangakkara et al (1995), Kaya et al (2001).…”
Section: Plant Dry Matter Yield (G/pot)supporting
confidence: 86%
“…Potassium also increases the fixation of nitrogen by promoting root development in plants. Abdalla and Abdelwahab (1995), as a result of the study of the element in the plant, the water level of potassium in the plant body and roots have found that increase the yield of dry matter.…”
Section: Introductionmentioning
confidence: 99%
“…Results of field experiments at Kanpur (India) showed that foliar sprays of 2% KCl at flowering increased grain yield and WUE of chickpea. WUE, with foliar sprays ofKCl was 16-17 kg grain ha-Imm water as compared to 14-15 kg grain ha-I-mm water in the control (Ali 1985)_ Abd-Alla andWahab (1995) working on water stressed faba beans found that applying KO at 150 mg kg-I soil, helped alleviate moisture stress and enhanced N fixation_ The use of 'Jalshakti', a water absorbing polymer is also promising in increasing moisture availability. At Kanpur (India), soil incorporation of Jalshakti at 12 kg ha-I or furrow placement at 2 kg ha-I at sowing enhanced yield of chickpea by 12% over the control Ali (1994) (fable 9).…”
Section: Efficient Use Of Watermentioning
confidence: 99%
“…Moreover, K is required to maintain plant health, synthesize protein and starch, and enhance photosynthesis. In addition, potassium is one of the essential nutrients needed for biological N fixation and nodule formation (Abd‐Alla & Wahab, 1995; Duke et al., 1980). Potassium is also vital in maintaining nitrogenase activity per unit root weight and per unit nodule weight of legumes (Høgh‐Jensen, 2003).…”
Section: Resultsmentioning
confidence: 99%